An inside out journey: biogenesis, ultrastructure and proteomic characterisation of the ectoparasitic flatworm Sparicotyle chrysophrii extracellular vesicles - Riera-Ferrer, Enrique; Mazanec, Hynek; Mladineo, Ivona; Konik, Peter; Piazzon, M Carla; Kuchta, Roman; Palenzuela, Oswaldo; Estensoro, Itziar; Sotillo, Javier; Sitjà-Bobadilla, Ariadna (Parasites & vectors, 2024)
BACKGROUND: Helminth extracellular vesicles (EVs) are known to have a three-way communication function among parasitic helminths, their host and the host-associated microbiota. They are considered biological containers that may carry virulence factors, being therefore appealing as therapeutic and prophylactic target candidates. This study aims to describe and characterise EVs secreted by Sparicotyle chrysophrii (Polyopisthocotyla: Microcotylidae), a blood-feeding gill parasite of gilthead seabream (Sparus aurata), causing significant economic losses in Mediterranean aquaculture. METHODS: To identify proteins involved in extracellular vesicle biogenesis, genomic datasets from S. chrysophrii were mined in silico using known protein sequences from Clonorchis spp., Echinococcus spp., Fasciola spp., Fasciolopsis spp., Opisthorchis spp., Paragonimus spp. and Schistosoma spp. The location and ultrastructure of EVs were visualised by transmission electron microscopy after fixing adult S. chrysophrii specimens by high-pressure freezing and freeze substitution. EVs were isolated and purified from adult S. chrysophrii (n = 200) using a newly developed ultracentrifugation-size-exclusion chromatography protocol for Polyopisthocotyla, and EVs were characterised via nanoparticle tracking analysis and tandem mass spectrometry. RESULTS: Fifty-nine proteins involved in EV biogenesis were identified in S. chrysophrii, and EVs compatible with ectosomes were observed in the syncytial layer of the haptoral region lining the clamps. The isolated and purified nanoparticles had a mean size of 251.8 nm and yielded 1.71 × 108 particles · mL-1. The protein composition analysis identified proteins related to peptide hydrolases, GTPases, EF-hand domain proteins, aerobic energy metabolism, anticoagulant/lipid-binding, haem detoxification, iron transport, EV biogenesis-related, vesicle-trafficking and other cytoskeletal-related proteins. Several identified proteins, such as leucyl and alanyl aminopeptidases, calpain, ferritin, dynein light chain, 14-3-3, heat shock protein 70, annexin, tubulin, glutathione S-transferase, superoxide dismutase, enolase and fructose-bisphosphate aldolase, have already been proposed as target candidates for therapeutic or prophylactic purposes. CONCLUSIONS: We have unambiguously demonstrated for the first time to our knowledge the secretion of EVs by an ectoparasitic flatworm, inferring their biogenesis machinery at a genomic and transcriptomic level, and by identifying their location and protein composition. The identification of multiple therapeutic targets among EVs' protein repertoire provides opportunities for target-based drug discovery and vaccine development for the first time in Polyopisthocotyla (sensu Monogenea), and in a fish-ectoparasite model.
Keywords: Electron microscopy; Exosomes; extracelulární vezikuly; Monogenea; Platyhelminths; Sea Bream; Prophylactic target candidates; Ectosomes; Peptidases; proteomika; Extracellular Vesicles; Animals; zvířata; Drug target candidates; Trematoda; ploštěnci; Proteomics; Polyopisthocotyla; mořan zlatý